E-invoice authenticity verification scheme based on signature verification - Rongna XIE; Weihua MAO; Guozhen SHI (网络与信息安全学报)
With the rapid development of network and information technology,paperless and electronic have become the development trend of today's economic life.As a consumption certificate,electronic invoices have become more and more demanding in e-commerce.The existing electronic invoice verification method is to inquire the invoice information in the national electronic account base according to the invoice number,invoice code,billing date,and amount,and realize the function of comparison inquiry,and can not detect the fraudulent behavior of issuing invoices by non-issuing institutions,and cannot guarantee the full legality and authenticity of electronic invoices.Aiming at the above problems,a verification scheme for electronic invoice authenticity based on signature authentication was proposed.By verifying the signature of the tax agency,the legality verification of the blank electronic invoice is verified,and the digital signature of the seller is verified to determine the authenticity of the invoiced content.Ensure that the electronic invoices passed for verification are true and reliable.